THE USE OF CODE-MIXING BY SOUTH JAKARTAN YOUTH IN TWITTER - Aina Deneta (LINGUA LITERA : journal of english linguistics and literature, 2021)
Abstract Youth and language are two inseparable things. In communication, youth usually have their way of communication. In form of written communication, youth mostly use code-mixing, especially in social media. Based on this phenomenon, this research attempts to analyze 20 posts by South Jakartan Youth on Twitter from September to October 2018 that contained code-mixing. The writer applied qualitative research and the theory of code-mixing by Mckay and Nancy. In those posts on Twitter by South Jakartan youth, the writer found three forms of codemixing; insertions, phrases insertions, and sentence insertions.